2019
DOI: 10.1136/bmjopen-2018-023927
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific intergenerational trends in morbidity burden and multimorbidity status in Hong Kong community: an age-period-cohort analysis of repeated population surveys

Abstract: ObjectivesPrevalence of multimorbidity has been increasing worldwide. While population ageing undoubtedly contributes, secular trends have seldom been decomposed into age, period and cohort effects to investigate intergenerational differences. This study examines the birth cohort effect on morbidity burden and multimorbidity in Hong Kong community.DesignSex-specific age-period-cohort analysis with repeated cross-sectional surveys.SettingA territory-wide population survey database.Participants69 636 adults aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 40 publications
0
17
0
2
Order By: Relevance
“…The rising trend in physician-diagnosed hypertension in Hong Kong could have partially been driven by the heightened health awareness and detection over time 15,17 , along with a growing number of local health education programs in the community as well as an earlier and more proactive detection in the primary care setting 18–20 . While the increasingly prevalent obesity, as a major risk factor to most cardiovascular events, may have contributed to the rise in hypertension, recent local research on validation of self-reported hypertension against the objective clinical data showed an improved case reporting as the level of sensitivity increased between 2003/04 and 2014/15 (Chung GK, 2019, unpublished data), which led to a rise in self-reported prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The rising trend in physician-diagnosed hypertension in Hong Kong could have partially been driven by the heightened health awareness and detection over time 15,17 , along with a growing number of local health education programs in the community as well as an earlier and more proactive detection in the primary care setting 18–20 . While the increasingly prevalent obesity, as a major risk factor to most cardiovascular events, may have contributed to the rise in hypertension, recent local research on validation of self-reported hypertension against the objective clinical data showed an improved case reporting as the level of sensitivity increased between 2003/04 and 2014/15 (Chung GK, 2019, unpublished data), which led to a rise in self-reported prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…A trend analysis was realised in Hong Kong with 69,636 adults aged 35 or over who participated in the surveys in 1999, 2001, 2005 and 2008. Multimorbidity was de ned as presenting two or more chronic conditions from a list of 14 8 . Further, a study conducted in Canada with data of 1996-97, 2005 and 2012-13 identi ed an increase in the prevalence of multimorbidity that may be attributed to an increase of obesity 26 .…”
Section: Resultsmentioning
confidence: 99%
“…This research took into account three types of chronic diseases: diabetes, pulmonary and cardiovascular diseases, and stated that their results may show an underestimation of the real situation, because other chronic multimorbidity diseases, like arthrosis, were left out of consideration 7 . Another aspect that needs to be studied further is the association of multimorbidity with gender, since women have been associated with multimorbidity in some countries 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Multimorbidity, defined as the co‐occurrence of two or more chronic health conditions, has been shown to be associated with more healthcare utilization (Glynn et al, 2011; Lai, Wong, et al, 2019), lower quality of life (Fortin et al, 2004; Lai, Ma, & Hou, 2019), and frailty (Gobbens, van Assen, Luijkx, Wijnen‐Sponselee, & Schols, 2010). Prevalence of multimorbidity has been increasing worldwide, mainly due to the rapid aging of populations in the developed world (Fu, Huang, & Chou, 2014; Lai, Guthrie, et al, 2019; Van Oostrom et al, 2016). It has been estimated that prevalence among people aged 50 years or more ranged from 45.1% to 71.9% (Garin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%